THE ANALYSIS OF PROMOTION MIX AFFECTING CUSTOMER PURCHASE DECISION TO BUY WOMEN’S CLOTHING VIA ONLINE STORE - Tritanti, Ruella Juniar; nu, Arma (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study is explanatory research, in accordance with purpose to describe the causal relationship among variables through hypothesis testing. This research aims to examine the effect of Promotion Mix on Customer Purchasing Decision at Online Store. The hypothesis analysis is about simultaneous effect, partial effect and dominant factor, were conducted in order to acknowledge the relationships among the independent variables (Advertising, Personal Selling, Sales Promotion, Public Relation and Direct Marketing) on Customer’s Purchasing Decision. The samples and population of this study were students of economic and business faculty of Brawijaya University as customer of online store. In this study, the data collection method by distributing 100 questitionaire. The sampling technique used is Purposive sampling and the research instruments were tested using the validity test, reliability test, and classical assumption test. The hypothesis testing used the F test and t test in Multiple Regression Analysis. The multiple regression analysis showed that simultaneously, Advertising, Sales Promotion, Direct Marketing, Personal Selling, and Public Relation had significant effect on Customer Purchasing Decision. Meanwhile, partial test shows that the variables of Advertising, Personal Selling, and Public Relation had significant effect on Customer Purchasing Decision. However, the variables of Sales Promotion and Direct Marketing had no significant effect on Customer’s Purchasing Decision. The dominant test shows that Advertise has dominant effect on customer’s purchasing decision. Keywords: Promotion Mix, advertise, personal selling, sales promotion, public relation, direct marketing, customer’s purchasing decision.